Introduction to quantum electronics - Unger, Hans-Georg, 1926- (International series of monographs in natural philosophy ;, 1970)
Introduction to Quantum Electronics is based on a one-semester lecture of electrical engineering for German students. The book is an introduction to the fundamentals of lasers and masers and a presentation of the principles of physics, their theory, and methods of analysis that seek to analyze, explain, and quantify related important phenomena. The properties of a laser is then discussed, the author comparing it to the properties of the maser. Although masers are based on the same physical properties as that of the lasers, masers amplify microwaves by induced emission. How the laser is amplif.